Social Aspects of Learning:Sámi People in the Circumpolar North - Laiti, Outi Kaarina; Frangou, Satu-Maarit (International Journal of Multicultural Education, 2019)
This article addresses how, in the Arctic regions, indigenous traditional educational approaches focus on the cultural background of the people and their social learning customs in today’s context. The development of Arctic pedagogical approaches is discussed in light of experiences collected in Finnish Lapland in 2017 with the Sámi people. Particularly, the significance of social interactions in indigenous pedagogies is explored. We ask how social interactions benefit technologically enhanced learning in the Sámi cultural context. The findings suggest that social interactions have the potential for improving learning even when learning with and through information and communication technologies (ICTs).